The effectiveness of parent management training in a Brazilian sample of patients with oppositional-defiant disorder (Archives of Clinical Psychiatry, 2005)
BACKGROUND: Oppositional-defiant disorder (ODD) is considered a hard to treat condition. The aim of this study was to assess the effect of parent management training (PMT) on the symptoms of ODD and conduct disorder (CD) in Brazilian children with ODD. METHODS: We conducted a clinical evaluation in which data was analyzed from parents of five patients with ODD who participated in a PMT group. The ODD and CD symptoms were assessed before and at least a month after they started participating in the group. The outcome measures were rating scales based on the DSM-IV criteria for ODD and CD. RESULTS: Most patients continued to fulfill criteria for ODD, but the severity of their ODD symptoms was reduced 48,75%. The difference between the means on the severity scale of ODD symptoms was statistically significant (p= 0,031) The fulfillment of criteria for CD was largely diminished. CONCLUSIONS: PMT was effective for the reduction of ODD and CD symptoms in patients with ODD. PMT may represent a valuable therapeutic option for patients with ODD in different cultures.